1983
DOI: 10.1002/cite.330551011
|View full text |Cite
|
Sign up to set email alerts
|

Flüssigphasenrückvermischung in Blasensäulenreaktoren

Abstract: Die Untersuchung der axialen Durchmischung der Fliissigphase in Abhangigkeit von den Stoff-, Betriebs-und Konstruktionsparametern war Gegenstand zahlreicher Forschungsarbeiten, die z. B. in Literatur-Ubersichten von Westphely [I] und Shah et al. [2] zusammengefaljt worden sind. Die Mehrzahl der veroffentlichten Arbeiten wurde an relativ kleinen Versuchsreaktoren bei nur geringen Gasbelastungen durchgefiihrt. Aus industrieller Sicht besteht jedoch ein verstarktes Interesse an Untersuchungen an groBen Reaktoren,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The validity of this relationship is also proven by the experimental results of Deckwer [4] and Weinspach et al [14]. The energy balance of the built-in heat exchanger can be reduced to the terms for convection and heat transfer.…”
Section: Modelingmentioning
confidence: 59%
See 1 more Smart Citation
“…The validity of this relationship is also proven by the experimental results of Deckwer [4] and Weinspach et al [14]. The energy balance of the built-in heat exchanger can be reduced to the terms for convection and heat transfer.…”
Section: Modelingmentioning
confidence: 59%
“…The equation by Weinspach et al [14] was explicitly developed to take into account column internals, such as sidefed heat exchangers.…”
Section: Model Parametersmentioning
confidence: 99%
“…This is a realistic figure as it was evaluated in experiments in a bubble column with such a diameter D [14].…”
Section: Bubble-induced Liquid Circulationmentioning
confidence: 99%
“…Wendt [15] presented a correlation for D ax including results from experiments at a bubble column with a diameter of 1 m. For a superficial gas velocity v Go of 2 cm/s Wendt found a dispersion coefficient of 0.25 m 2 /s. Using Eq.…”
Section: Axial Mixing Of Liquid Phasementioning
confidence: 99%
“…Hence for the same level of mixing in both the axial and radial direction it should be: H 2 / D ax = (D/2) 2 / D rad (14) or with H = 20 m and D = 4.6 m: D rad = 0.013´D ax (15) But with the previously calculated values for D ax and D rad it was found that D rad = 0.19´D ax (16) Thus mixing in the radial direction is faster than in the axial direction. Only axial dispersion is relevant to the total mixing behavior in the liquid phase.…”
Section: Calculations For Reactor Designmentioning
confidence: 99%